Exploring epigenetic drift and rare epivariations in amyotrophic lateral sclerosis by epigenome-wide association study - Brusati, Alberto; Peverelli, Silvia; Calzari, Luciano; Tiloca, Cinzia; Casiraghi, Valeria; Sorce, Marta Nice; Invernizzi, Sabrina; Carbone, Erika; Cavagnola, Rebecca; Verde, Federico; Silani, Vincenzo; Ticozzi, Nicola; et al. (Frontiers in Aging Neuroscience, 2023)
During the last decades, our knowledge about the genetic architecture of sporadic amyotrophic lateral sclerosis (sALS) has significantly increased. However, besides the recognized genetic risk factors, also the environment is supposed to have a role in disease pathogenesis. Epigenetic modifications reflect the results of the interaction between environmental factors and genes and may play a role in the development and progression of ALS. A recent epigenome-wide association study (EWAS) in blood identified differentially methylated positions mapping to 42 genes involved in cholesterol biosynthesis and immune-related pathways. Here we performed a genome-wide DNA methylation analysis in the blood of an Italian cohort of 61 sALS patients and 61 healthy controls. Initially, a conventional genome-wide association analysis was performed, and results were subsequently integrated with the findings from the previous EWAS using a meta-analytical approach. To delve deeper into the significant outcomes, over-representation analysis (ORA) was employed. Moreover, the epigenetic signature obtained from the meta-analysis was examined to determine potential associations with chemical compounds, utilizing the Toxicogenomic Database. Expanding the scope of the epigenetic analysis, we explored both epigenetic drift and rare epivariations. Notably, we observed an elevated epigenetic drift in sALS patients compared to controls, both at a global and single gene level. Interestingly, epigenetic drift at a single gene level revealed an enrichment of genes related to the neurotrophin signaling pathway. Moreover, for the first time, we identified rare epivariations exclusively enriched in sALS cases associated with 153 genes, 88 of whom with a strong expression in cerebral areas. Overall, our study reinforces the evidence that epigenetics may contribute to the pathogenesis of ALS and that epigenetic drift may be a useful diagnostic marker. Moreover, this study suggests the potential role of epivariations in ALS.